Exploring the Relationship between Teachers’ Socio-economic Status and Their Teaching Profession Attitude at Secondary School Level - Tanveer Iqbal Mughal, Mushtaq-ur-Rehman Siddiqui, (PJE, 2023)
The main focus of this study was to find out the relationship between teachers’ socio-economic status (SES) and their teaching profession attitude at secondary school level in the province of Punjab. After extensive literature review and focus group discussion, four subcomponents of teachers’ SES have been selected named as qualification, income, occupational respect, wealth and while teaching values, attributes, salaries & incentives, and satisfaction with teaching profession were selected as sub-components of teaching profession attitude. A questionnaire was surveyed on nine-hundred (900) teachers who taught science subjects to secondary classes and selected from all over the Punjab through proportionate stratified random sampling technique. The major findings showed positive relationship between the both variables of the study while teachers’ occupational respect- only one of the subcomponents of teachers’ SES found positive relationship with teaching profession attitude. This study recommended that public and media should play its role to promote the occupational respect of teachers in the eyes of general public and all stakeholders